Effect of vitamin E succinate on inflammatory cytokines induced by high-intensity interval training - Hadi Sarir; Ghodsieh Emdadifard; Homayoun Farhangfar; Hossein TaheriChadorneshin (Journal of Research in Medical Sciences, 2015)
Aim and Scope: The anti-inflammatory effect of vitamin E under moderate exercises has been evaluated. However, the effect of vitamin E succinate, which has more potent anti-inflammatory effect than other isomers of vitamin E has not been evaluated. Therefore, the aim of the present study was to evaluate the effects of vitamin E succinate on tumor necrosis factor alpha (TNF-a) and interleukin-6 (IL-6) production induced by high-intensity interval training (HIIT). Materials and Methods: In the present study, 24 rats were randomly divided into control (C), supplementation (S), HIIT, and HIIT + supplementation (HIIT+S) groups. HIIT training protocol on a treadmill (at a speed of 40-54 m/min) and vitamin E succinate supplementation (60 mg/kg/day) was conducted for 6 weeks. Results: Serum IL-6 in the HIIT group significantly increased compared with the C group (350.42 ± 123.31 pg/mL vs 158.60 ± 41.96 pg/mL; P = 0.002). Also, serum TNF-a concentrations significantly enhanced (718.15 ± 133.42 pg/mL vs 350.87 ± 64.93 pg/mL; P = 0.001) in the HIIT group compared with the C group. Treatment of the training group with vitamin E numerically reduced IL-6 and TNF-a when compared with the HIIT group (217.31 ± 29.21 and 510.23 ± 217.88, respectively, P > 0.05). However, no significant changes were observed in serum TNF-a (P = 0.31) and IL-6 (P = 0.52) concentrations in the HIIT + S group compared with the C group. Conclusion: HIIT-induced IL-6 and TNF-α decreased by administration of Vitamin E succinate.